Caracterização da silagem da rama da batata doce emurchecida e adicionada de fubá de milho como aditivo - Corrêa, Annelise Aragão (2016)
The objective of this study was to investigate the fermentative and nutritional characteristics of sweet potato (Ipomoea batatas) vine silage using different levels of corn meal as additive. A completely randomized design consisting of seven levels of the additive (0, 5, 10, 15, 20, 25 and 30% corn meal) and four replicates was used, totaling 28 laboratory mini-silos (experimental units). The different levels of additive in sweet potato vine silage exerted quadratic effects on the content of dry matter (DM), crude protein (CP), neutral detergent insoluble protein (NDIP), acid detergent insoluble protein (ADIP), and total carbohydrates. There was an increase in DM content with inclusion of the additive and CP was reduced from 11.23% (no additive) to 9.46% (30% additive) in sweet potato vine silage. NDIP and ADIP content was lower in sweet potato vine silage containing 30% additive (1.15% and 0.70%, respectively). No significant differences in organic matter, ashes, ether extract, neutral detergent fiber, acid detergent fiber, or total digestible nutrients were observed between the different levels of additive. Regarding fermentative parameters, a quadratic effect of sweet potato vine silage containing different additive levels was observed on pH, ammoniacal nitrogen as a percentage of total nitrogen [N-NH3 (%NT)], and losses from gases and effluent. A lower pH was observed at a level of the additive of 15% (3.31) and higher values at levels of 20%, 25% and 30% (3.88, 3.89 and 3.88, respectively). The N-NH3 values (%NT) ranged from 2.84% (no additive) to 3.59% (15% additive), and the lowest loss from gases and effluents was 2.38% DM and 199 kg/t in sweet potato vine silages containing 30% and 10% additive, respectively. Sweet potato vine is a good-quality roughage alternative that can be stored as silage, as along as a water-absorbing additive such as corn meal is used at a level no less than 20%.